Pemodelan Adopsi Alat Pembelajaran Berbasis AI dalam Pendidikan Guru - Viernes, Valerie Jane Fontanilla; A. Palapuz, Noel (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Integrating Artificial Intelligence (AI) in education reshapes teaching and learning, particularly in teacher education. This literature review investigates the adoption of AI-powered learning tools, focusing on pre-service mathematics teachers. It synthesizes cognitive factors such as perceived usefulness (PU), perceived ease of use (PEOU), prior exposure to AI tools, psychological factors like self-efficacy, and social influences like peer support and institutional support. Ethical concerns surrounding perceived trust, technological readiness, and attitudes toward AI in education are examined. Theoretical frameworks like the Unified Theory of Acceptance and Use of Technology (UTAUT) and Bandura’s self-efficacy theory are applied to understand AI adoption dynamics. The review finds that PU, PEOU, and institutional support are key predictors of AI adoption, while ethical barriers and technical readiness remain significant challenges. Recommendations are provided for overcoming these barriers to ensure equitable access to AI in teacher education.